2013
DOI: 10.1177/0954008313509390
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of aluminum oxide-coated carbon nanotubes and the properties of composite epoxy coatings research

Abstract: Multiwalled carbon nanotubes (MWCNTs) were acidized to get MWCNTs-COOH; the aluminum oxide (Al 2 O 3 )-coated MWCNTs hybrid material were prepared by sol-gel method and the result of cladding was verified using x-ray diffraction and scanning electron microscopy. Silane-coupling agent (KH560) was used to modify the hybrid materials. Composite coating with different concentrations of MWCNTs and Al 2 O 3 -coated MWCNTs was prepared. The wear resistance of the composite coating was tested by wear tester. The imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…7(c) indicates that the impedance of coating conformed to the organic coating at the initial soaking, and the data in Fig. 7(e) is consistent with the model at the mid-soaking soaking [22,[30][31][32]. Thus, the transition time was 16 h for pure epoxy, and 42, 66, and 90 h for 2wt.% GO/epoxy, 2wt.% nano-TiO 2 /epoxy, and 2wt.% TiO 2 -GO/epoxy, respectively.…”
Section: Corrosion Resistance Of Coatingssupporting
confidence: 78%
See 2 more Smart Citations
“…7(c) indicates that the impedance of coating conformed to the organic coating at the initial soaking, and the data in Fig. 7(e) is consistent with the model at the mid-soaking soaking [22,[30][31][32]. Thus, the transition time was 16 h for pure epoxy, and 42, 66, and 90 h for 2wt.% GO/epoxy, 2wt.% nano-TiO 2 /epoxy, and 2wt.% TiO 2 -GO/epoxy, respectively.…”
Section: Corrosion Resistance Of Coatingssupporting
confidence: 78%
“…Besides, redundant emulsion was carefully poured into a homemade container, respectively. Finally, The epoxy-coated steels and cured epoxy coatings were attained using two steps: steels and containers were baking in an oven at 120 °C for 1 h followed by 220 °C for other 1.5 h [22]. The dry film thickness of coatings was required to be measured utilizing screw micrometer and calibrator.…”
Section: Preparation Of Composite Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the seriflux mixture was sprayed on the surface of the steel after ultrasonic oscillation and mechanical stirring, degassed in a vacuum oven at room temperature for 0.5 h, and cured with the following cycle: 120 for 1 h and 220 for 2 h [33]. The pure epoxy sample was also prepared under the same curing condition.…”
Section: Preparation Of the Go Nano-al 2 O 3 And Go-al 2 O 3 Composimentioning
confidence: 99%
“…(a) and 8(b) displayed the impedance spectra of the composite coatings (2wt.% GO/epoxy, 2wt.% Al 2 O 3 /epoxy, and 2wt.% GO-Al 2 O 3 /epoxy) and the pure epoxy after 108 h, 142 h, 240 h and 60 h of immersion, respectively, which indicated that the impedance of coating conformed to the organic coating at the last corrosion state[33,[45][46][47]. The results verified that the GO-Al 2 O 3 nanocomposites exhibited the higher anti-corrosion performance of epoxy coatings than Al 2 O 3 and GO, which owed to well dispersion and the excellent inherent plugging micro-pores performance.…”
mentioning
confidence: 95%